GLUCOCORTICOID-INDUCED ALTERATION OF THE SURFACE MEMBRANE OF CULTURED HEPATOMA CELLS - Ballard, Philip L. (The Rockefeller University Press, 1970)
Glucocorticoids induce an alteration of the surface of hepatoma tissue culture (HTC) cells as expressed by changes in cell electrophoretic, antigenic, and adhesive properties. The alteration is assayed by the increased adhesiveness of induced cells for a glass surface. The induction process has a lag period of about 3 hr and attains a plateau level after 24–30 hr when 50–80% of the steroid-treated cells are firmly adhered. Less than 10% of untreated cells adhere under the same conditions. Induction is inhibited by actinomycin D and cycloheximide, demonstrates both pH and temperature dependence, and responds to changes in steroid concentration and structure. By contrast, the attachment per se of preinduced cells is not affected by inhibitors of RNA and protein synthesis, fluctuations of temperature and pH, and the presence or absence of the hormone. When the induction process is reversed by removal of steroid or addition of actinomycin D, preinduced adhesiveness is lost with a half-life of 13–24 hr, but in the presence of cycloheximide the loss is accelerated (t(1/2) 3–5.5 hr). These results suggest that glucocorticoids induce the biosynthesis of a protein which either modifies the cell surface (an enzyme) or is incorporated into surface structures (structural protein).